The Analysis of Financial Statements Performance: Case Studies PT. Bank Negara Indonesia (Persero) - Rombe, Yusuf (Manunggal Halim Jaya, 2021)
The objectiveness of this study is to determine the level of growth in financial performance at PT. BNI (Persero) Tbk; starts from period 2013 to 2015. This assessment is carried out to determine how the bank's financial performance in the last few periods will be and what the conditions will be like in the coming period (forecast). That this will be useful in describing how financial performance has a vital role in a bank's business continuity so that in this study use descriptive qualitative approach. The result of this study is the growth in the financial performance is increasing from a liquidity perspective, considering that only two percentage ratios in 2015 underperformed in 2013, namely the investing policy ratio and the banking ratio. According to data shown before, the increase in the financial performance viewed from a profitability perspective is dominated by a volatile percentage ratio. There are two ratios whose performance continues to decline (e.g., Net Profit Margin and Return on Equity). According to the previous data proven, there is a gap between liquidity ratio and profitability ratio, given that the growth in the liquidity performance has increased. On the other hand, the change in profitability performance has decreased.